WATER SOLUBILITY IN A CALCIUM ALUMINOSILICATE MELT - McMillan P.; Holloway J.; Peraudeau G.; Coutures J.P. (My University, 1986)
We have measured the water solubility between 1 atmosphere and 5 kilobars for a calcium aluminosilicate melt of molar composition CaO 0.28, Al2O3 0.06, SiO2 0.66 (An9Wo38Qz53). The water contents were measured via thermogravimetric analysis of isobarically quenched glasses, and range from 0.121 wt% H2O near 1 aim to 9.25 wt% H2O at 5 kilobars. The molar water solubility lies between those of SiO2 and albite melts below around three kilobars, and crosses the albite solubility curve above this pressure. The present results are compared with data in the literature on related calcium aluminosilicate melts. There seems to be little variation of water solubility with composition for calcium aluminosilicate melts, unlike analogous alkali aluminosilicate compositions. Examination of the data suggests that there may be a maximum in molar water solubility along the albite-anorthite join.